(untitled) (SCAFFOLD: A SHOWCASE OF VANDERBILT FIRST-YEAR WRITING, 2020)
This essay, written for a first-year writing seminar in history, explores two literary works’ depictions of American identity in the Cold War. The author notes similarities and differences in the novels’ portrayal of American idealism: idealizing freedom is central to American identity in both novels, but this idealism takes on contrasting approaches and is guided by different assumptions. For additional context, listen to the author’s reflection on the piece below.